2005
DOI: 10.1179/oeh.2005.11.2.138
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Blood Lead Levels and Neurobehavioral Function in Children Living in Chennai, India

Abstract: The relationship between blood lead level and neurodevelopment was assessed in a pilot cross-sectional study of 74 4-14-year-old children in Chennai, India. Mean blood lead level was 11.1 microg/dL (2.5-38.3). The Binet-Kamath IQ test and the Wide Range Assessment of Visual Motor Activity (WRAVMA) were administered to 58 children. Teachers completed the Connor's Behavioral Rating Scale. Excluding two outliers, IQ and WRAVMA composite scores were inversely related to blood lead level, with an effect size of app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 17 publications
0
20
0
1
Order By: Relevance
“…Lead exposure is particularly concerning in developing countries where children have higher blood lead concentrations than in the US or Europe. 1517 The present study examined the association between blood lead concentration (mean = 6.4 µg/dL) and behavioral problems using data from a community sample of Chinese preschool children.…”
Section: Introductionmentioning
confidence: 99%
“…Lead exposure is particularly concerning in developing countries where children have higher blood lead concentrations than in the US or Europe. 1517 The present study examined the association between blood lead concentration (mean = 6.4 µg/dL) and behavioral problems using data from a community sample of Chinese preschool children.…”
Section: Introductionmentioning
confidence: 99%
“…This includes lowered intelligence, behavioral problems, deficits in academic achievements, and problem solving, as well as reductions in visual/spatial, motor, and language skills [13]. Thanks to public health and regulatory activities the BLL significantly decreased, however, still many studies have found adverse effects of levels below 10  μ g/dL.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several clinical studies investigated the effects of low-level prenatal and perinatal lead exposure on intellectual development in children and found that mater-derived lead exposure would have a more powerful and lasting impact on neurobehavioral development of offspring than postnatal exposure [23-27]. Actually, even very low level of maternal blood lead (10 μg/dL) may induce intelligence quotient changes in the child [2].…”
Section: Introductionmentioning
confidence: 99%